Population Dynamics of Lactobacillus helveticus in Swiss Gruyère-Type Cheese Manufactured With Natural Whey Cultures - Moser, Aline; Schafroth, Karl; Meile, Leo; Egger, Lotti; Badertscher, René; Irmler, Stefan (Frontiers in Microbiology, 2018)
Lactobacillus helveticus, a ubiquitous bacterial species in natural whey cultures used for Swiss Gruyère cheese production, is considered to have crucial functions for cheese ripening such as enhancing proteolysis. We tracked the diversity and abundance of L. helveticus strains during six months of ripening in eight Swiss Gruyère-type cheeses using a culture-independent typing method. The study showed that the L. helveticus population present in natural whey cultures persisted in cheese and demonstrated a stable multi-strain coexistence during cheese ripening. With regard to proteolysis, one of the eight L. helveticus populations exhibited less protein degradation during ripening.